WATER CONTENT, FAT CONTENT, AND ACIDITY DEGREE OF SMOKED SALTED EGGS WITH THE ADDITION OF GINGER AND TURMERIC - Kusmayadi, Andri; Solahudin, Ari; Frasiska, Nurul (Jurnal Teknologi Hasil Peternakan, 2026)
Duck eggs contain high protein, but are easily damaged, so preservation is needed. One way of preservation is salting, either through the wet method (salt soaking) or dry (salt wrapping). This process aims to preserve eggs, reduce the fishy smell, and provide a distinctive taste. In addition, salted eggs can also be preserved through smoking, which can extend their shelf life and can be enriched with herbal ingredients such as ginger and turmeric. Research on the effects of turmeric and ginger is expected to improve the quality, durability, and nutritional content of salted eggs. This study aims to examine the effect of adding ginger and turmeric on the water content, fat content, and pH of herbal smoked salted eggs, and to determine the optimal concentration of the two herbal ingredients that can affect the water content, fat content, and pH of herbal smoked salted eggs. The materials used in this study included 100 duck eggs, salt, brick, ash, turmeric, and ginger. The study was conducted using a completely randomized design (CRD) method, involving 4 treatments and 5 replications. The treatments applied in this study were variations in the addition of herbal ingredients, namely 0%, 7.5% turmeric, 7.5% ginger, and a combination of 7.5% turmeric with 7.5% ginger. The results showed that the addition of herbal ingredients with different concentrations significantly affected the water content and fat content of herbal smoked salted eggs (P <0.01), but did not significantly affect the pH value (P <0.05). The addition of 7.5% ginger and a combination of 7.5% ginger + 7.5% turmeric produced the best water content, while the best fat content was obtained from a combination of 7.5% ginger + 7.5% turmeric.